ANALISIS SPASIAL-TEMPORAL PENANGKAPAN IKAN PELAGIS DI PERAIRAN KABUPATEN BARRU - Muhammad Yusran Lalogau; Abdul Rauf; Hasrun Abdullah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
This study aims to conduct spatial and temporal analysis of boat chart fisheries in Barru Regency by (1) mapping potential fishing areas, (2) analyzing the status of fish resource utilization in the Boat chart in Sumpang Binangae Village, Barru Regency. This research was conducted in February-March 2019 in the waters of Barru Regency which is a fishing base boat chart in Sumpang Binangae Village, Barru Regency. The data used are catch data and fishing location data as well as oceanographic data (sea surface temperature and chlorophyll-a concentration) in February and March 2019 collected from the download of Satellite Images, Provincial Fisheries Service statistics from 2007-2017 to Barru Regency area. Analysis of the determination of potential fishing areas with boat charts using geographic information systems (GIS), analyzing the status of utilization of fisheries resources is used analysis of maximum sustainable potential (MSY) and optimum fishing (fopt) by analyzing the effort of catch per unit effort (CPUE). The results showed that Sea surface temperature (SST) in February and March of small pelagic fish in the waters of Barru Regency favored warm waters with a range of SST 28.61 oC - 29.7 oC waters and productivity of Chlorophyll-a range of 0.44-0.0 94 mg / m3. The highest catch in March is in the waters of the western part of Barru Regency, which is 1391 - 2060 Kg. Utilization rate (Tp) Anchovy in the new regency in the last 10 years, namely in 2008 - 2017 has not yet passed JTB so that its utilization still needs to be improved.